Plan estratégico para la concesionaria de vehículos Cinascar Cía. Ltda.; de la ciudad de Loja, periodo 2014-2019 - Ramón Mancheno, Noemí de los Ángeles (2015)
This thesis "STRATEGIC PLAN FOR THE CAR DEALER CINASCAR CIA. LTDA. LOJA CITY, PERIOD 2014-2019 ", will propose oriented strategies based on internal and external analysis in which the clinical develops. For this, a survey was performed to all customers of the company are 150, also surveyed 15 employees of CINASCAR and interview the manager of the company was conducted. For information on the competition, they stated questions were asked in the interview with the manager, who is the one with greater knowledge of the subject. The main results of the market research are: The 56.67% of customers perceive the service as very good over 14.67% perceived it as excellent. The 100% of customers CINASCAR states that the vehicle you purchased this dealer covered their expectations. The 57.33% of customers would buy if another vehicle at this dealership. The 84.00% of users of vehicles if CINASCAR recommend to their friends and acquaintances to buy a car is the dealer. According to 71.33% of customers they learned of the existence of concessionaire through friends and colleagues. The 57.33% of customers prefer CINASCAR cancel your car in cash. According to 70.67% preferred as a means of communication to local television. 100% of customers require promotions for the purchase of your vehicle. The main promotion is discounted and free maintenance. With regard to external factors affecting the dealer are: CINASCAR has a strong threat as the import quota is intended for this brand of vehicle. The main opportunity for the company is to exploit the market segment represented by female heads of households is increasing. Its main weaknesses are lack of stock of vehicles and the final approach to advertising that the company has. Its main strength is that CINASCAR service offered is perceived as good for customers visiting the dealership. When performing an analysis of Porter's 5 forces are among the main findings fierce rivalry between competitors and Chevrolet, and Nissan amrcas Hiundai addition to the threat of substitute products with the entry of electric vehicles to other dealers as country Lojacar and they have in Ecuador. The weighting of the EFE matrix gives a score of 2 means that the company is not avoiding threats. While the outcome of the IFE Matrix is 2.70 indicating that the company has a strong domestic position. Pursuant to the results, the strategic plan, whose main objective is to position the brand in the lojana citizenship arises. To do they arise six goals to be developed over five years. It starts proposing strategies to sell 2015 vehicles; anticipate selling about competition vehicles with airbag that they still do not have them; gather all models sold in Ecuador so that customers have the opportunity to personally meet and perform test drives to encourage their purchase; reach the target audience of the company through the media they prefer; and finally, to train all company employees in specific areas of your workspace and general subjects in sales, customer service, corporate objectives, after sales service. All this plan requires an investment of $ 57,335 which includes updating the website, exhibitions of vehicles, training human talent. This budget includes activities during the five year strategic plan, including advertising and training